2016
DOI: 10.22159/ajpcr.2016.v9s2.13405
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness Regarding Antibiotic Prophylaxis for Infective Endocarditis Among Undergraduate Dental Students

Abstract: Objective: To evaluate the knowledge and awareness regarding antibiotic prophylaxis for infective endocarditis (IE) among undergraduate dental students. Methods:A validated questionnaire of 16 questions, regarding the basic knowledge and awareness about antibiotic prophylaxis for the prevention of IE, was distributed among 100 students randomly belonging to final year and internship (5 th year trainee) of the undergraduate dental program in Saveetha Dental College and Hospital, Saveetha University, Chennai. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 17 publications
0
52
1
Order By: Relevance
“…This finding is in accordance with Kumar and Harshini, who found all the students (100%) take personal history and Okoh and Enabulele, found 96.7 % of students take habit history. [2,8] This might be due to the fact that most of the students have knowledge about the role of tobacco and alcohol in causing oral cancer. Whereas Fotedar et al in their study found only 67.7% of students took history about the use of tobacco and alcohol.…”
Section: Section: Dentistry Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in accordance with Kumar and Harshini, who found all the students (100%) take personal history and Okoh and Enabulele, found 96.7 % of students take habit history. [2,8] This might be due to the fact that most of the students have knowledge about the role of tobacco and alcohol in causing oral cancer. Whereas Fotedar et al in their study found only 67.7% of students took history about the use of tobacco and alcohol.…”
Section: Section: Dentistry Discussionmentioning
confidence: 99%
“…However Kumar and Harshini found 86 % of students take family history and Anderson Rocha-Buelvas et al found 22.58% evaluate family history of cancer. [2,10] 78% of students inform patients about the risk factors of oral cancer. However Kumar and Harshini found only 33 % of students inform their patients about the risk factors, whereas Bhagavathula et al found 98.2% students inform.…”
Section: Section: Dentistry Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other substances may also be added such as grated coconut or spices like aniseed, peppermint, cardamom and cloves, based on the local preference.Tobacco which is a basic ingredient, is associated with an increased risk of oral. [23] cancer. The lime releases reactive oxygen species from extracts of areca-nut which might be the contributing factor for cytogenic damage involved in oral cancer.…”
Section: Quidmentioning
confidence: 99%
“…9 The American Heart Association has published many journals to guide people ways to avoid infective endocarditis since ever since 1955. 10 However, since the publication of the 2007 version guidelines, the American Heart Association/American College of Cardiology (AHA/ACC) strategies have been updated several times, most recently in the 2017 AHA/ACC. 11,12 Due to these repeated updates in guidelines, dental practitioners should always have up-to-date information about the latest procedures on the usage of antibiotics for the inhibition of ineffective endocarditis.…”
Section: Introductionmentioning
confidence: 99%